(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
This research aimed to improve students’ in writing ability using think talk write strategy at the tenth grade of SMA Swasta Perguruan Keluarga. The problem of the research is Can the Think Talk Write (TTW) strategy to improve the students’ writing skill at the tenth grade of SMA Yayasan Perguruan Keluarga Pematang Siantar?. The objective of the research is to improve the students’ writing skill in descriptive text at the tenth grade of SMA Yayasan Perguruan Keluarga Pematang Siantar using the think talk write strategy. The research is quantitative research with Experimental research design by using the pre-experimental research methods with one group pretest-posttest design. For the data collection, there were pre-test and post-test. The population of this research 212 students’ in research academic year 2023/2024 with of 35 students’ was the sample. It used a purposive sampling. The data analysis was at tenth grade students’ stared from scoring pre-test and post- test and finding the different mean of the score. Based on the data analysis, the writer finding pre-test students’ mean score 59,23 and after the treatment, the writer used to post-test to know students’ improve writing ability score. The result of the test found the average of the pos-test mean score test was 82,97 . The different of the score was significant. It means that using think talk write strategy in teaching cam improve the students’ writing skill